A Two-Step Compressed Spectrum Sensing Scheme for Wideband Cognitive Radio - Shengnan Yan (Dianxin kexue)
A two-step compressed spectrum sensing scheme for wideband cognitive radio was proposed in order to reduce the huge data transmission overhead of the traditional DCS scheme.The CS reconstruction of this scheme was divided into two steps,i.e.the information fusion for the support set and the joint recovery of multiple signals,and the prior information obtained from the former step can guide the joint recovery of the latter step.Simulation results show that this scheme can achieve better performance than the traditional DCS scheme as long as 50% of users are involved in the joint recovery,which means that this scheme can reduce the data transmission overhead and save energy consumed greatly.